DISCRIMINATION AGAINST FAT PEOPLE AND PERSONS WITH PHYSICAL AND MENTAL DISABILITIES / DISCRIMINAREA PERSOANELOR OBEZE ȘI CU DIZABILITĂȚI FIZICE ȘI PSIHICE - PERJU DUMBRAVĂ, Dan; DANCIU, Adina; CHIROBAN, Ovidiu; GHERMAN, Cristian; RADU, Carmen (Studia Universitatis Babeş-Bolyai Bioethica, 2015)
Discrimination against Overweight People and Persons with Physical and Mental Disabilities. Discrimination is one of the reasons why equality is not respected. This implies differentiation, exclusion, restriction and preferential treatment between individuals, groups and communities, in some of these disadvantages. All these choices, decisions, actions, are made based on non-objective criteria. Generally, people with disabilities are among the most discriminated groups, because the society believes that only perfectly healthy people are able to work. In the category of those with disabilities, enter those with mental disabilities, too. These people are marginalized, excluded by society and people look them with distrust and indifference. Another category discriminated and an extremely sensitive topic of discussion is the category of obese people, which obviously suffer from various forms of discrimination in employment, at a public event, at the school, when supporting a speach, in the air traffic, in health care. Discriminarea persoanelor obeze și cu dizabilități fizice și psihice. Discriminarea este unul dintre motivele pentru care egalitatea nu este respectată. Acest fapt implică diferențiere, excludere, restricție și tratament preferențial între indivizi, grupuri și comunități, în termen de dezavantaje. Toate aceste alegeri, decizii, acțiuni sunt realizate pe baza unor criterii non-obiective. În general, persoanele cu dizabilități sunt printre cele mai discriminate grupuri, deoarece societatea consideră că numai oamenii perfect sănătoși sunt capabili să lucreze. În categoria persoanelor cu dizabilități intră și cei cu dizabilități mentale. Acești oameni sunt marginalizați, excluși de societate și sunt priviți cu neîncredere și indiferență. O altă categorie discriminată și un subiect extrem de sensibil este categoria de persoane obeze, care, evident, suferă de diferite forme de discriminare la locul de muncă, la un eveniment public, la școală, atunci când susțin un discurs, în traficul aerian, în îngrijirile medicale. Cuvinte-cheie: discriminare, persoane cu dizabilități fizice și mentale, obezitate